2008
DOI: 10.1002/ejoc.200800704
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Domino Metathesis of 7‐Oxanorbornenes and Its Application to the Synthesis of Biologically Active Glutamate Analogues

Abstract: A highly regioselective domino metathesis reaction of 7-oxanorbornene was developed that employed an intramolecular association of an amide carbonyl group to a ruthenium metal centre. By using this reaction, twelve glutamate analogues inspired by dysiherbaine were efficiently synthesized over 12-14 steps; one of the analogues exhibited bioactivity consistent with central nervous system depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Indeed, we have recently successfully demonstrated the usefulness of this effect in the development of biologically active glutamate analogues. [16] Regiocontrol is one of the major concerns in metathesis reactions. [5,[25][26][27][28] Works directed towards the use of the associating effect in other types of metathesis reactions are in progress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, we have recently successfully demonstrated the usefulness of this effect in the development of biologically active glutamate analogues. [16] Regiocontrol is one of the major concerns in metathesis reactions. [5,[25][26][27][28] Works directed towards the use of the associating effect in other types of metathesis reactions are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…[5,29,31] In this context, we have further studied the associating effects of neighboring carbonyl functional groups in the domino metathesis of 7-oxanorbornenes, and have found that the effect essentially provides high level of regioselectivity in this reaction. [16] However, it should be noted here that a mechanism based on [2+2] cycloaddition/cycloreversion [5] can be also operative in the reaction of C-type 7-oxanorbornene 25. In this mechanism, the first ROM reaction by [Ru]=CH 2 takes place in an unselective manner, and all reaction intermediates finally lead to thermodynamically stable F-type prod-Scheme 7.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[16] Scheme 14. Synthesis of glutamate analogues by elaboration of the adduct derived from a tandem Ugi/Diels-Alder reaction sequence.…”
Section: Applications Of the Ugi-derived Norbornane/ Norbornene Derivmentioning
confidence: 99%